2013
DOI: 10.1586/17446651.2013.827380
|View full text |Cite
|
Sign up to set email alerts
|

The role of progesterone and the progesterone receptor in human reproduction and cancer

Abstract: Insufficient progesterone, effect possibly more on immune factors rather than adequate endometrial development, can be an easy remedial cause of infertility by simply supplementing the luteal phase with either vaginal or intramuscular or oral (dydrogesterone) progesterone. Progesterone will also help to reduce miscarriage rates when follicle maturing drugs are used for those with regular menses but follicular maturation defects, or women with recurrent miscarriages. One mechanism of action seems to be related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 132 publications
0
54
0
Order By: Relevance
“…Despite clinical evidence of its efficacy, there does not appear to be at this present time, except at extremely low serum levels of P, a good method to determine who requires supplementation and who does not [26]. Equally important, if certain women are found to need progesterone, how can one determine if the amount given has corrected the problem?…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Despite clinical evidence of its efficacy, there does not appear to be at this present time, except at extremely low serum levels of P, a good method to determine who requires supplementation and who does not [26]. Equally important, if certain women are found to need progesterone, how can one determine if the amount given has corrected the problem?…”
Section: Discussionmentioning
confidence: 96%
“…Progesterone has been found to not only increase the serum PIBF but to also increase the level of a PIBF intracellular splice variant (that is similar in size to circulating PIBF) in rapidly growing cells, e.g., the cells of the fetal placental unit (or cancer cells) [1,25,26]. The progesterone receptor modulator abortifacient mifepristone has been found to decrease intracytoplasmic PIBF production of the 34-36-kDa intracytoplasmic splice variant [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second case examined in this study, which is reported here, had non-small cell lung cancer that progressed despite multiple courses of chemotherapy or immunotherapy with nivolumab. This case report documents a positive response to single agent mifepristone, which activates the immune destruction of the tumor by inhibiting intracytoplasmic PIBF by blocking extranuclear membrane P receptors (7,16).…”
mentioning
confidence: 69%
“…The hypothesized mechanism of action of mifepristone is that this progesterone receptor modulator suppresses a progesterone-associated immunomodulatory protein that is unique to rapidly growing cells in the fetal placental unit, including embryonic, mesenchymal, and trophoblast cells, and in rapidly growing cancer cells. This protein is called the progesterone induced blocking factor (PIBF) (5)(6)(7)(8).…”
mentioning
confidence: 99%